PENGARUH PROMOSI, KUALITAS, DAN PACKAGING TERHADAP MINAT PEMBELIAN MIE LETHEK KULINER KHAS BANTUL - Nur Wahyuni (Jurnal Socia Akademika, 2022)
Yogyakarta is one of Indonesia's various regions with diversity, uniqueness, and excellence, especially in the culinary field. One of the areas with its distinctive culinary is Bantul with "Mie Lethek," which is already known by the general public. In the marketing of Lethek Noodles related to people's buying interest, there are several influential factors, such as promotion, quality, and packaging. The design of this study is to use a quantitative type of research that aims to determine the influence of promotion, quality, and packaging on the interest in buying Lethek Noodles in the community. The population and samples in this study were all consumers who had purchased Lethek Noodle products, which was 40 people determined by accidental sampling techniques. The source of research data is primary data obtained from closed questionnaires. Data analysis techniques use multiple linear regression. The results showed that quality and packaging positively and significantly influenced the Buying Interest of Lethek Noodle consumers partially with a Sig. Value of 0.012 and 0.038 while promotion did not have a positive and significant influence on the Buying Interest of Lethek Noodle consumers partially based on the value of Sig. of 0.534. The results of simultaneous regression tests show that Promotion, Quality, and Packaging positively and significantly influence the buying interest of Lethek Noodle consumers together based on the Sig value. of 0.005